Avaliação estrutural de ônibus rodoviário com aplicação de plataformas elevatórias para prover acessibilidade - Aderichn, Laercio (2014)
Every citizen has the right to come and go, and the government has to ensure this right for everyone including people with disabilities or reduced mobility. The accessibility issue is widely discussed in the national scene, and in the last decade, Brazil officiated by its actions, the concern and willingness to achieve the social inclusion of disabled people. Several actions have been implemented as: development of regulatory standards, Decrees emissions, Laws and Ordinances on the rules to be followed towards accessibility and also penalties for those whom do not follow or respect them. Researchers have found that road buses of medium and long distances have not changed and did not provide favorable conditions of accessibility for disabled people. The goal of this study is to analyze the whole structure of a road bus body with platform lifts application to provide accessibility, verify its resilience and suggest solutions to enable the structure that will receive. The structural arrangement studied is submitted to the installation of two types of lifts developed for road buses, which are compared with a model reference without these devices for boundary crossing, already experimentally validated. With the finite element analysis realization was possible to evaluate the values of stresses acting on the car bodies and the rigidity of the arrangements through modal analysis, concluded that the structures tend not to fail with the inclusion of the lifts in this bus body model.